Water-in-acid gel polymer electrolyte realized through a phosphoric acid-enriched polyelectrolyte matrix toward solid-state supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Torris, Arun A. T.; Chandran, Nikhil M. K.; Nair, Sanoop B.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2018)
A new concept of water-in-acid gel polymer electrolytes (GPEs) is introduced. The simple and scalable UV-light-assisted synthesis of a copolymer matrix possessing polyelectrolyte behavior, followed by swelling in minimally diluted H3PO4 (15.1 M/88 wt % aqueous solution), effects formation of a high proton-conducting, self-standing, and mechanically stable polyelectrolyte GPE (PGPE). Retention of high mechanical stability despite the presence of a large amount of liquid species makes it a promising candidate for replacing conventional GPEs. The high proton conductivity (9.8 X 10(-2) S cm(-1)) of the PGPE at an ambient temperature of 303 K is attributed to the high concentration of the conducting species present in the polymer matrix. The PGPE-based polyaniline (PANI) supercapacitor device (PANI-1) with a mass loading of 1 mg cm(-2) exhibits a high specific gravimetric capacitance of 385 F g(-1) at a current density of 0.25 mA cm(-2). At the same current density, the PANI-5 device retains high gravimetric and areal capacitance values of 258 F g(-1) and 1288 mF cm(-2), respectively. The low equivalent series resistance value of 0.78 Omega (for the PANI-5 device) further proves the excellent electrode-electrolyte interface formed by the water-in-acid GPE. A 100% capacitance retention even after 9000 continuous charge-discharge cycles strongly indicates the feasibility of adopting water-in-acid GPEs in future supercapacitors.

Weak intermolecular interactions in covalent organic framework-carbon nanofiber based crystalline yet flexible devices - Mohammed, Abdul Khayum; Vijayakumar, Vidyanand; Halder, Arjun; Ghosh, Meena; Addicoat, Matthew; Bansode, Umesh; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2019)
<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">The redox-active and porous structural backbone of covalent organic frameworks (COFs) can facilitate high-performance electrochemical energy storage devices. However, the utilities of such 2D materials as supercapacitor electrodes in advanced self-charging power-pack systems have been obstructed due to the poor electrical conductivity and subsequent indigent performance. Herein, we report an effective strategy to enhance the electrical conductivity of COF thin sheets through the in situ solid-state inclusion of carbon nanofibers (CNF) into the COF precursor matrix. The obtained COF-CNF hybrids possess a significant intermolecular π···π interaction between COF and the graphene layers of the CNF. As a result, these COF-CNF hybrids (DqTp-CNF and DqDaTp-CNF) exhibit good electrical conductivity (0.25 × 10<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–3<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> S cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">), as well as high performance in electrochemical energy storage (DqTp-CNF: 464 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">). Also, the fabricated, mechanically strong quasi-solid-state supercapacitor (DqDaTp-CNF SC) delivered an ultrahigh device capacitance of 167 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.5 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">. Furthermore, we integrated a monolithic photovoltaic self-charging power pack by assembling DqDaTp-CNF SC with a perovskite solar cell. The fabricated self-charging power pack delivered excellent performance in the areal capacitance (42 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">) at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> after photocharging for 300 s.